2019
DOI: 10.1007/s40747-019-00123-5
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative filtering recommendation algorithm based on user correlation and evolutionary clustering

Abstract: In recent years, application of recommendation algorithm in real life such as Amazon, Taobao is getting universal, but it is not perfect yet. A few problems need to be solved such as sparse data and low recommended accuracy. Collaborative filtering is a mature algorithm in the recommended systems, but there are still some problems. In this paper, a novel collaborative filtering recommendation algorithm based on user correlation and evolutionary clustering is presented. Firstly, score matrix is pre-processed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 21 publications
(27 reference statements)
0
37
0
Order By: Relevance
“…Results of two-tailed t -tests are similar to one-tailed results for two datasets. Katarya and Verma [49] Priyankka et al [51] Chen et al [48] Pradeep and Bhaskar [47] Mohapatra et al [50] Our Approach RMSE values Zhou et al [37,52] Chen and others [48] Yu et al [37,53] Sarwar et al [37,55] Hinton [37,56] Papadakis et al [37,57] Sanandaj and Alizadeh [37] Siddiquee et al [13] Our Approach RMSE values Figure 5. Comparison of RMSE values with different studies for Movielens 1M dataset.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Results of two-tailed t -tests are similar to one-tailed results for two datasets. Katarya and Verma [49] Priyankka et al [51] Chen et al [48] Pradeep and Bhaskar [47] Mohapatra et al [50] Our Approach RMSE values Zhou et al [37,52] Chen and others [48] Yu et al [37,53] Sarwar et al [37,55] Hinton [37,56] Papadakis et al [37,57] Sanandaj and Alizadeh [37] Siddiquee et al [13] Our Approach RMSE values Figure 5. Comparison of RMSE values with different studies for Movielens 1M dataset.…”
Section: Performance Evaluationmentioning
confidence: 99%
“…The main limitation of collaborative filtering systems is that it suffers from limited data information expandability and the problem to a cold start [12]. Mansur et al [14] have observed common challenges across most collaborative filtering algorithms, including difficulty in providing recommendations to new users, limited trust in the conclusions made from small data, user data privacy, and sparsity of data [15] [16].…”
Section: Collaborative Filteringmentioning
confidence: 99%
“…In [25] [27] [26] [28], novel heterogeneous evolutionary clustering algorithms are presented. The goal of these algorithms is to gather users with similar interest into the same cluster and to help users find items that fit their personal tastes best.…”
Section: Evolutionary Computing In Recommender Systemsmentioning
confidence: 99%
“…In [28], a novel collaborative filtering recommendation algorithm based on user correlation and evolutionary clustering is presented. Firstly, score matrix is pre-processed with normalization and dimension reduction.…”
Section: Evolutionary Computing In Recommender Systemsmentioning
confidence: 99%